2007
DOI: 10.17221/2261-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of olive cake on daily gain, carcass characteristics and chemical composition of lamb meat

Abstract: This experiment investigated the effect of olive cake in the feed of weaned Pramenka lambs on their daily gain, carcass traits and on the chemical composition of different groups of muscles. For that purpose, 45 male lambs were divided into three groups with 15 lambs each and fed separately for 50 days. The first group (control) was fed a commercial concentrate, while the second and third (test) groups were fed a concentrate with the addition of 15% and 30% olive cake, respectively. The results showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
34
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 10 publications
9
34
1
Order By: Relevance
“…Our results were not in agreement with those reported by Mioč et al (2007), who reported lower weights for the liver, hide and legs and higher weights for the stomach and intestines (P≤0.05) in lambs fed a diet containing 30% olive cake for 50 days. Similarly, Mioč et al (2007) did not find any differences in lung and heart weights as a result of olive cake addition.…”
Section: Body Componentscontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results were not in agreement with those reported by Mioč et al (2007), who reported lower weights for the liver, hide and legs and higher weights for the stomach and intestines (P≤0.05) in lambs fed a diet containing 30% olive cake for 50 days. Similarly, Mioč et al (2007) did not find any differences in lung and heart weights as a result of olive cake addition.…”
Section: Body Componentscontrasting
confidence: 99%
“…In regard to the other carcass traits, Mioč et al (2007) found that lambs receiving the highest olive cake diet (30%) presented lower HCW and carcass yield than those fed the control diet or a diet with 15% of olive cake. Aboayasha et al (1982), Belibasakis (1985) TA 48 groups.…”
Section: Main Carcass Traitsmentioning
confidence: 96%
“…In a previous study, Mioc et al (2007) reported no adverse effects of the inclusion at 15% on DM intake of whole dried and whole olive cake in the diet of finishing lambs, respectively; although when olive cake was added at 30% on DM intake, an adverse effect on the average daily gain was found. In the present study, the OC diet contained nearly 25% of olive cake.…”
Section: Resultsmentioning
confidence: 81%
“…However, the lack of negative effects on the growing performance suggested that the stoning process could have improved the digestibility of the diet as already observed by Sadeghi et al (2009), using experimental diets containing 20% of stoned olive cake. The dietary treatment did not affect slaughtering performance according to previous studies that included comparable amounts of stoned olive cake or vegetable fat in the diet of finishing lambs (Mioc et al, 2007;Berthelot et al, 2010;Noci et al, 2011).…”
Section: Resultsmentioning
confidence: 94%
“…The results are in accordance with Ragni et al (2003) and Zein Al-Abdein Kewan, (2012) who didn't find any significant differences on body weight, feed intake and feed conversion ratio in lambs fed with 20% olive pomace and 10% lime treated olive pulp respectively. Mioc et al (2007), found that replacement of 15% of maize with olive cake in the concentrate of lambs had no significant difference in daily gain, carcass weight and dressing percentage as compared to control group that received a commercial feed for fattening.…”
Section: Resultsmentioning
confidence: 90%